Strategic Growth Options - Kulatilaka, Nalin; Perotti, Enrico C. (Management Science, 1998)
We provide a strategic rationale for growth options under uncertainty and imperfect competition. In a market with strategic competition, investment confers a greater capability to take advantage of future growth opportunities. This strategic advantage leads to the capture of a greater share of the market, either by dissuading entry or by inducing competitors to “make room” for the stronger competitor. As a result of this strategic effect, payoffs are in a rough sense more convex than in the case of no investment in a growth option. When the strategic advantage is strong, increased uncertainty encourages investment in growth options: higher uncertainty means more opportunity rather than simply larger risk. If the strategic effect is weak, the reverse is true. On the other hand, an increase in systematic risk discourages the acquisition of growth options. Our results contradict the view that volatility is a strong disincentive for investment.